Development of a Diagnostic PCR Assay for Detection of Schistosoma Species - Ali, Tabish; Jabbar, Hamza; Ullah Khan, Mirza Muhammad Saad; Azhar, Talha; Tasleem, Humaira; Shahid, Ifra; Bibi, Tahira; Nashin, Savera; Ullah, Qamar; Said, Arsalan (Biological and Clinical Sciences Research Journal, 2026)
Schistosomiasis remains one of the most important neglected tropical diseases worldwide and continues to impose a substantial public health burden. Accurate, sensitive, and specific diagnostic tools are essential for effective case detection, surveillance, and control programs. Objective: To develop and evaluate a polymerase chain reaction (PCR)-based diagnostic assay for the detection of Schistosoma species in clinical samples. Methods: This laboratory-based diagnostic accuracy study was conducted at Bahauddin Zakariya University, Multan, Punjab, Pakistan. A total of 40 biological samples, including stool and urine specimens, were analyzed to assess the performance of a newly developed PCR assay for detecting Schistosoma species. The assay was evaluated against a reference diagnostic method. Diagnostic performance was determined by calculating sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy. Receiver operating characteristic analysis was performed to determine discriminatory ability and optimal cycle threshold cut-off. Correlation analysis was also carried out to assess the relationship between DNA concentration and cycle threshold values, while analytical specificity was examined by testing for cross-reactivity with non-target organisms. Statistical significance was considered at p<0.05. Results: The PCR assay demonstrated high diagnostic performance, with a sensitivity of 90.0%, specificity of 95.0%, and overall diagnostic accuracy of 92.5%. The positive predictive value was 94.7%, while the negative predictive value was 90.5%, indicating a strong ability to differentiate infected from non-infected samples. A significant correlation was observed between PCR findings and the reference method (p<0.001). Receiver operating characteristic analysis showed excellent discriminatory capacity, with an area under the curve of approximately 0.94 and an optimal cycle threshold cut-off value of ≤35. A strong negative correlation was found between DNA concentration and cycle threshold values, reflecting good amplification kinetics. The assay also showed high analytical specificity, as no cross-reactivity was observed with non-target organisms. Although the assay reliably detected low concentrations of target DNA, a few false-negative results occurred near the limit of detection. Conclusion: The developed PCR assay showed high sensitivity, specificity, and overall diagnostic accuracy for the detection of Schistosoma species in clinical samples. It may serve as a reliable molecular tool for clinical diagnosis and epidemiological surveillance of schistosomiasis.